Pengaruh konsentrasi tepung pisang ambon dan penambahan Lactobacillus casei terhadap karakteristik kimia yogurt sinbiotik - Handayani, Isti; Nuraini, Nuraini (Universitas Muhammadiyah Mataram, 2022)
Synbiotic yogurt is a yogurt that contains probiotics and prebiotics and is one type of functional food. This study aims to determine the effect of the addition of L. casei and ambon banana flour on the chemical characteristics of synbiotic yogurt. The study was conducted using a randomized group design with two treatments, namely the type of starter and the concentration of ambon banana flour. Starters used: 1) Steptococcus thermophilus and Lactobacillus bulgaricus; 2) Steptococcus thermophillus, Lactobacillus bulgaricus, and Lactobacillus casei. The concentration of added banana flour is as follows: 0; 2,5; 5,0; 7,5; and 10%. The observed variables include pH, total titrated acid, and reduction sugar. The results showed that the addition of L. casei to yogurt culture increased pH, total titrated acid, and reduction sugar. Where, the increase in the concentration of ambon banana flour decreases the pH and sugar reduction but increases the total titrated acid yogurt.